2015
DOI: 10.3390/f6103686
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rhizobia Inoculation on Biomass Gain and Tissue Nitrogen Content of Leucaena leucocephala Seedlings under Drought

Abstract: Anticipated increases in the frequency of heat waves and drought spells may have negative effects on the ability of leguminous trees to fix nitrogen (N). In seedlings of Leucaena leucocephala inoculated with Mesorhizobium loti or Rhizobium tropici, we investigated how the developmental stage and a short drought influenced overall biomass and the accumulation of carbon and N in plant tissues. In early developmental stages, the number of nodules and nodule biomass were correlated with total plant biomass and δ 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 53 publications
(51 reference statements)
0
10
0
4
Order By: Relevance
“…Generally, populations of rhizobia capable of nodulation the specific native legumes are abundant in soils of regions, where the species are native (Bala et al, 2003). However, L. leucocephala is an exotic legume species, native to Central America, and yet has nodulation in all soils, possibly due to the high promiscuity of this species, which is able to establish symbiosis with rhizobia of the genus Rhizobium (Pereyra et al, 2015), Mesorhizobium (Rangel et al, 2016), Sinorhizobium (Xu et al, 2014), Bradyrhizobium (Wang et al, 2006), and Cupriavidus (Florentino et al, 2009), Inoculation with native isolates of Rhizobia has significantly increased shoot biomass and symbiotic effectiveness compared to the recommended and noninoculated plants. The accumulation of nitrogen in shoot dry matter is normally used to estimate the symbiotic efficiency of nitrogen fixation of the native rhizobia according to Lima et al (2012) and Calheiros et al (2015).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, populations of rhizobia capable of nodulation the specific native legumes are abundant in soils of regions, where the species are native (Bala et al, 2003). However, L. leucocephala is an exotic legume species, native to Central America, and yet has nodulation in all soils, possibly due to the high promiscuity of this species, which is able to establish symbiosis with rhizobia of the genus Rhizobium (Pereyra et al, 2015), Mesorhizobium (Rangel et al, 2016), Sinorhizobium (Xu et al, 2014), Bradyrhizobium (Wang et al, 2006), and Cupriavidus (Florentino et al, 2009), Inoculation with native isolates of Rhizobia has significantly increased shoot biomass and symbiotic effectiveness compared to the recommended and noninoculated plants. The accumulation of nitrogen in shoot dry matter is normally used to estimate the symbiotic efficiency of nitrogen fixation of the native rhizobia according to Lima et al (2012) and Calheiros et al (2015).…”
Section: Discussionmentioning
confidence: 99%
“…(Fabaceae) é uma espécie arbórea originária da América Central cultivada como planta forrageira, mas que reúne vários atributos típicos de espécies invasoras (Melo-Silva et al, 2014). No Brasil, a espécie é popularmente conhecida como leucena (Fonseca & Jacobi, 2011) e indicada para composição de sistemas agroflorestais (Pereyra et al, 2015), principalmente em regiões de clima semiárido (Walker, 2012), devido ao seu rápido crescimento e alto valor nutricional de minerais e proteínas (Crawford et al, 2015).…”
Section: Introductionunclassified
“…In the past, several studies have shown that inoculation of Acacia with Bradyrhizobium spp. significantly enhance growth of Acacia seedlings (Galiana et al, 1990(Galiana et al, , 1994Dumroese et al, 2009;Pereyra et al, 2015). Martin-Laurent et al (1999) showed that inoculation with the indigenous Malaysian strains Bradyrhizobium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Author(s) agree that this article remains permanently open access under the terms of the Creative Commons Attribution License 4.0 International License Bradyrhizobium spp., Azorhizobium spp., and Mesorhizobium sp.) and form nitrogen-fixing nodules, which can fix nitrogen from air and supply nitrogen nutrient to trees for growth and development (Ferro et al, 2000;Zerhari et al, 2000;Dumroese et al, 2009;Ceccon et al, 2011;Diouf et al, 2015;Pereyra et al, 2015). Several studies have demonstrated that inoculation of seedlings (Oryza sativa, Glycine max and Zea mays) with rhizobial strains results in the change of root morphology, that is, increases in nodules, lateral roots, root hairs, root surface area, and total root length (Huang and Ladha, 1997;Ikeda, 1999;Souleimanov et al, 2002).…”
Section: Introductionmentioning
confidence: 99%